Passing Through: An Ethnography of Performance in Aceh’s Margins - Lariat, Joni (Curtin University, 2018)
This thesis contributes to the emergent field of queer anthropology by proposing a research methodology that prioritises queer embodied knowledge and sensory explorations of place. Based upon fieldwork in Sabang, this research examines the regulation of sexuality and gender from Aceh’s geographical and cultural margins. The implementation of punitive shari’ah in Aceh and the amplification of anti-LGBT rhetoric throughout Indonesia, make this research a significant addition to studies of Acehnese and Indonesian contemporary socio-cultural politics.